Biodegradation of p-cresol by Pseudomonas spp. Issue 7 (7th February 2016) - Hamitouche, A.; Bendjama, Z.; Amrane, A.; Kaouah, F.
Abstract: Phenols are toxic to several biochemical reactions . However, biological transformation of phenols to nontoxic entities exists in specialized microbes, owing to enzymatic potential involving enzymes of aromatic catabolic pathways. In this study, a series of experiments were performed to examine the effects of the mineral medium composition and the pH on p-cresol removal. In this purpose, p-cresol biodegradation was carried out in a batch reactor containing mixed bacteria; the temperature (30°C), the stirring velocity (200 rpm), the KH2 PO4 concentration (1.5 g/L), the K2 HPO4 concentration (2 g/L), and p-cresol concentration (100 mg/L) were kept constants. The initial pH was varied in the range 5–9 and the mineral components were tested in the following concentration ranges: 0–2 g/L for Nitrogen sources (NH4 Cl, KNO3, and NH4 NO3 ), 0–0.5 g/L for NaCl, and 0–0.2 g/L for MgSO4 . Their effects on p-cresol biodegradation and specific growth rate were examined. The shorter biodegradation time of p-cresol was 30.5 h for NH4 Cl, NaCl, and MgSO4 concentrations of 1, 0.3, and 0.1 g/L, respectively. Maximum specific growth rate (0.34 h −1 ) and total p-cresol removal were recorded for an optimal pH value of 8.